IMPLEMENTASI MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV PADA MATERI MANFAAT ENERGI MIS TUANKU HASYEM BANTA MUDA - Nasri Diana (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This study aims to determine the increase in student learning outcomes on the material benefits of energy after students learn through the implementation of the Discovery Learning Model. The research method is carried out using the CAR (Clasroom Action research) model which consists of the stages of planning, acting, observing and reflecting. The population in this study were all 4th grade students of MIS Tuanku Hasyem Banta Muda first semester 2020/2021. The sample in this study amounted to 29 people consisting of 13 male students and 16 female students. The data was collected by using lesson plans (RPP), student worksheets (LKS), student activity observation sheets (LOAS), and teacher activity observation sheets (LOAG). In the first cycle, the average value obtained by students was 63.10, with a percentage of completeness that was 58.62%. In the second cycle, the students' average score was 73.65, with a completeness percentage of 86.20%. In the third cycle, the students' learning outcomes increased maximally, which was marked by the acquisition of an average student score of 82.58 and the completeness KKK obtained 100 %, i.e. all students who participated in the second cycle of action learning obtained scores exceeding the predetermined Classical Completeness Criteria. Then the learning process with CAR was stopped in third cycle because it had reached the maximum KKM and KKK.